MODEL PEMBELAJARAN JIGSAW DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Arizal Fahmi (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to determine whether the application of a jigsaw cooperative learning model can improve student learning outcomes in mathematics learning in class X MAN 2 Pidie Jaya. This type of research is quantitative research. The design of this study is planning, design, implementation, evaluation, and reporting. Data analysis was performed descriptively. The results of the data analysis showed that the acquisition of the pre-test results of students 'mathematics learning with an average of 60. Then apply the jigsaw cooperative learning model for three meetings, at the end of the lesson a post-test evaluation is given to see the students' abilities after applying the jigsaw cooperative learning model. The results of data analysis showed that the students' mathematics learning pre-test results obtained an average of 84.4. Thus, it can be concluded, the jigsaw cooperative learning model can improve student learning outcomes.